EFFECT OF SOME CHEMICALS ON KEEPING QUALITY AND VASELIFE OF TUBEROSE (POLIANTHES TUBEROSA L.) CUT FLOWERS - Anjum, Muhammad Akbar; Naveed, Farrukh; Shakeel, Fariha; Amin, Shazia (Journal of Research (Science), 2001)
Cut spikes of tuberose were kept in CaCl2.2H2O, AgNO3, ascorbic acid and Tri-Miltox Forte (a fungicide) solutions with various concentrations to see their effects on keeping quality and vase–life of the flowers. A control (tap water) and a standard preservative were also included in the experiment. AgNO3, CaCl2.2H2O and Tri-Miltox Forte delayed flower opening as compared to ascorbic acid and standard preservative, but stood at par with control. CaCl2.2H2O at concentrations of 750 to 1250 ppm and Tri-Miltox Forte at 1500 ppm resulted in minimum flower wilting after six days. AgNO3 was found to have adverse effects on fragrance of the flowers. Water uptake by the spikes was more in those kept in standard preservative and CaCl2.2H2O 750 and 1000 ppm solutions. However, AgNO3 50 and 200 ppm solutions resulted in maximum vase-life (8 days) of cut flowers. Percentages of flowers opened and wilted were significantly negatively correlated with the vase-life. However, vase-life was not correlated with fragrance of the flowers and net water uptake.